2022
DOI: 10.1101/2022.06.24.497480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The cryo-EM structure of the CENP-A nucleosome in complex with ggKNL2

Abstract: Centromere protein A (CENP-A) nucleosome is an epigenetic marker that specifies centromere position. The Mis18 complex is a licensing factor for new CENP-A deposition via the CENP-A chaperone, Holliday junction recognition protein (HJURP) on the centromere chromatin. Chicken KINETOCHORE NULL2 (KNL2) (ggKNL2), a Mis18 complex component, has a CENP-C-like motif, and our previous study suggested that ggKNL2 directly binds to the CENP-A nucleosome to recruit HJURP/CENP-A to the centromere. However, the molecular b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 69 publications
(133 reference statements)
0
0
0
Order By: Relevance
“…Thus, we created a chimeric model combining AlphaFold2 predictions, which was independently validated twice with molecular dynamics for the stability (methods). This model aligns with the experimentally resolved structures, like the αKNL2 CENPC-k motif binds to histones similar to ggKNL2 (Figure 5A) (Jiang, et al 2022). Both SANTA domains interact with each other and contact all histones and DNA.…”
Section: βKnl2 Is Highly Dynamic and Loosely Bound To Centromeric Nuc...supporting
confidence: 85%
See 4 more Smart Citations
“…Thus, we created a chimeric model combining AlphaFold2 predictions, which was independently validated twice with molecular dynamics for the stability (methods). This model aligns with the experimentally resolved structures, like the αKNL2 CENPC-k motif binds to histones similar to ggKNL2 (Figure 5A) (Jiang, et al 2022). Both SANTA domains interact with each other and contact all histones and DNA.…”
Section: βKnl2 Is Highly Dynamic and Loosely Bound To Centromeric Nuc...supporting
confidence: 85%
“…Previous studies have shown that the M18BP1/KNL2 requires the CENPC-like motif for centromeric localization (Hori, et al 2017;Sandmann, et al 2017;Smith and Maddox 2017;Jiang, et al 2022).…”
Section: βKnl2 Depends On Cenpc-like Motif Containing Knl2 For Centr...mentioning
confidence: 98%
See 3 more Smart Citations